PENGARUH KEMAMPUAN WIRAUSAHA, PELUANG USAHA DAN TINGKAT PENDIDIKAN TERHADAP PENDAPATAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) SEKTOR KULINER DI KECAMATAN SOMBA OPU KABUPATEN GOWA - Armi Permana Putri; Agus Syam; Rahmatullah Rahmatullah; Muh. Ihsan Said; Muhammad Hasan (Politeknik Negeri Lhokseumawe, 2023)
The goal of this study was to ascertain how the education level, business possibilities, and entrepreneurial skills of MSMEs in the food service industry in Somba Opu District, Gowa Regency, impacted their revenue. This study falls under the quantitative descriptive research category. Through observation, surveys, and recording, data was gathered. 48 respondents made up the 48 samples in this study, which was followed by multiple regression analysis. (1) According to the findings of partial testing, business opportunity, degree of education, and entrepreneurial aptitude all had a favorable and substantial impact on the revenue of MSMEs in the culinary sector in Somba Opu District, Gowa Regency (2) The revenue of MSMEs in the food service industry in Somba Opu District, Gowa Regency is positively and significantly impacted by entrepreneurial potential, business prospects, and educational attainment. Keywords: Entrepreneurial Ability, Business Opportunity, Education Level MSME Income